Parental Guidance and Sharing of Information with Adolescents about Sexuality and Sexual Health: A review - Koirala, Manisa (Pragya Darshan प्रज्ञा दर्शन, 2023)
Sexual health is a fundamental to the overall health and well-being of individuals and families. Puberty is the process of physical changes as well as emotional maturation and being capable of sexual reproduction. Positive or respectful approach to sexuality and sexual relationships as well as free from coercion; discrimination and violence optimize the possibility of having pleasurable and safe sexual experiences. Appropriate pubertal guidance, sharing of information and education to youth about experiencing changes not only fostering positive attitudes but also healthy practices related to pubertal changes. It also influence on social and economic development of individual, communities as well as countries. This article intended to explore about the guidance and sharing of information practices of adolescence’s parents about pubertal changes and sexual health through literature search.